The measurement of racial discrimination in pay between job categories: theory and test - Örn B. Bodvarsson; John G. Sessions (Institute for the Study of Labor (IZA), 2008)
The traditional model of taste discrimination in labor markets presumes perfect substitution, making it unsuitable for the measurement of discrimination across job assignments. We extend the model to explain cross-assignment discrimination and test it on data from Major League Baseball. A competitive firm with a Generalized Leontief production function fills each job assignment with whites and nonwhites in an environment of customer prejudice. According to the model, cross-assignment discrimination depends upon racial productivity differences, the productivity x prejudice interaction, technology, relative labor supply and racial integration. We find strong evidence of ceteris paribus racial salary differences between hitters and pitchers.
urn:nbn:de:101:1-20081114118
Keywords: J7; 330; Wages; discrimination; imperfect substitutability; integration; Lohndifferenzierung; Ethnische Diskriminierung; Anforderungsprofil; Messung; Theorie; Professioneller Sport; USA